The Philippine fax directory for fast, accurate, easy communication nationwide. (Mahal Kong Pilipinas, 1991)
This 238-page publication is a complete listing of Fax numbers for the period 1993-94. It lists institutions and individuals fax numbers all over the country. It was published to further its use for business purposes. It has an index.